The Implementation Of Sleep Hygiene In Overcoming Sleep Disorders In Patients With Self-Care Deficit: Application Of King's Theory At Sawah Lebar Community Health Center, Bengkulu City Year 2025 - Nety Anggraini; Ramlis, Ravika (Utami Publisher, 2026)
Self-care deficit is the inability or difficulty in performing essential daily activities such as bathing, eating, dressing, and maintaining personal hygiene. The ability to perform self-care independently is crucial to maintaining physical and mental integrity as well as improving quality of life. The purpose of this study is to implement sleep hygiene in addressing sleep disorders in patients with self-care deficit using the application of King’s theory at Sawah Lebar Community Health Center, Bengkulu City, in 2025. The method used in this scientific paper is a case study involving 2 patients suffering from self-care deficit, taken from the working area of Sawah Lebar Community Health Center, Bengkulu City, by providing nursing care over 3 sessions. The results show that after 3 sessions, there was an improvement in the patients’ ability to care for themselves and a decrease in self-care deficit symptoms, along with an improvement in sleep quality experienced by the respondents through the application of sleep hygiene therapy. It can be concluded that sleep hygiene has a significant effect in overcoming sleep disorders in patients with self-care deficit. The researcher recommends that patients with sleep disorders and self-care deficits in the working area of Sawah Lebar Community Health Center, Bengkulu City, apply sleep hygiene to help manage sleep disorders.